A multipath methodology to promote ergonomics, safety and efficiency in agile factories. (18th January 2020) - Ceccacci, Silvia; Matteucci, Marco; Peruzzini, Margherita; Mengoni, Maura
An important area of risk management practice for manufacturing companies relates to the prevention of injuries and musculoskeletal disorders (MSDs). The greater benefits can be achieved where a preventive approach is used, based on ergonomic design of workplaces and attention to human requirements and limitations as well as human-machine interaction principles. The research aims at providing a pragmatic approach to support the application of ergonomic risk management in practice. It defines a multipath methodology to investigate human factors impacting on safety by considering the specific workspace, the adopted tools, the overall production environment and the workers' activity. An industrial case study is described to illustrate the methodology and demonstrate the benefits for companies. Results suggest that the proposed multipath methodology allow to effectively assist analysts in the definition of crucial risk factors and selection of proper ergonomics assessment and measurement tools according to the specific context of application.